2019
DOI: 10.1038/s41430-019-0403-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antenatal and infant micronutrient supplementation on middle childhood and early adolescent development outcomes in Tanzania

Abstract: Background: There is growing evidence that nutritional interventions in the first 1,000 days of life may influence long-term health and development outcomes. Few studies have examined the effect of maternal and infant micronutrient supplementation on development outcomes in sub-Saharan Africa. Methods: We conducted a follow-up study of two randomized trials of antenatal and infant micronutrient supplementation conducted in Dar es Salaam, Tanzania. We assessed the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Similarly, at 9–12 years of age, in a subsample of 10.5% of children (2879/27,356) alive at 12 weeks, procedural memory was improved by 0.11 SD (95% CI = 0.01, 0.20), but there was no difference in any of the six other developmental areas examined . Such largely null results were replicated in other cognitive follow‐up studies from China, Tanzania, and four separate studies from Bangladesh and Nepal …”
mentioning
confidence: 84%
“…Similarly, at 9–12 years of age, in a subsample of 10.5% of children (2879/27,356) alive at 12 weeks, procedural memory was improved by 0.11 SD (95% CI = 0.01, 0.20), but there was no difference in any of the six other developmental areas examined . Such largely null results were replicated in other cognitive follow‐up studies from China, Tanzania, and four separate studies from Bangladesh and Nepal …”
mentioning
confidence: 84%
“…Four studies assessed the long term effect of zinc supplementation with and without iron on child development in 6-9 year old children. All of them were supplemented before 36 months old [36,46,48,52]. These studies showed that zinc supplementation with and without iron does not have any long term effect on child mental and motor development in school age.…”
Section: Qualitative Analysis Findingsmentioning
confidence: 99%
“…Eleven studies only supplemented children with zinc alone [32, 33, 35, 38-41, 44, 45, 50, 54] and four studies co-supplemented them with zinc and iron [34,36,37,49]. Ten trials had three parallel arms that one arm received zinc and iron; another arm received iron; and the third arm received zinc alone [22,23,42,43,[46][47][48][51][52][53].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations